Atomic and mesoscopic structure of Dy-based surface alloys on noble metals. (1st March 2022) - Mousavion, Sina; Yu, Ka Man; Maniraj, Mahalingam; Lyu, Lu; Knippertz, Johannes; Stadtmüller, Benjamin; Aeschlimann, Martin
Abstract: Surface alloys are a highly flexible class of low dimensional materials with the opportunity to tune and control the spin and charge carrier functionalities on the nanoscale. Here, we focus on the atomic and mesoscopic structural details of three distinct binary rare-earth-noble metals (NM) surface alloys by employing scanning tunneling microscopy and low energy electron diffraction. Using Dysprosium as the guest element on fcc(111) NM substrates, we identify the formation of non-commensurate surface alloy superstructures, which lead to homogeneous moiré patterns for DyCu2 /Cu(111) and DyAu2 /Au(111), while an inhomogeneous one is found for DyAg2 /Ag(111). The local structure was analyzed for these samples and the observed differences are discussed in the light of the lattice mismatches of the alloy layer with respect to the underlying substrate. For the particularly intriguing case of a DyAg2 surface alloy, the surface alloy layer does not show a uniform long-range periodic structure, but consists of local hexagonal tiles separated by extended domain walls, which occur likely to relieve the in-plane strain within the DyAg2 surface alloy layer. Our findings clearly demonstrate that surface alloying is an intriguing tool to tailor the local atomic structure as well as the mesoscopic moiré structures of metallic heterostructures.